Prognostic and clinicopathological significance of mucin family members expression in gastric cancer: a meta-analysis - Wang, Shunda; Mu, Yongrun; Zhang, Jianwei; Wang, Chengfeng (Frontiers in Oncology, 2025)
BackgroundMucin family members have been reported to be widely expressed in gastric carcinoma with diverse functions. Several important mucins exert the function of tumorigenesis or progression in gastric cancer (GC). Here, we conduct this meta-analysis to evaluate the association between mucin expression and clinicopathological features in GC.MethodsLiterature searches were performed in PubMed, Embase, The Cochrane Library, and ISI Web of Science, and, finally, 28 studies met our criteria. Odds ratios or hazard ratios with 95% confidence intervals were calculated to evaluate the effect quantity. We analyzed the expression of MUC1, MUC2, MUC5AC, and MUC6 and their clinicopathological characteristics separately at the same time.ResultsTwenty-eight studies that contain 4,603 patients were included in our meta-analysis. MUC1 was associated with gender, Lauren classification, depth of tumor invasion, TNM, vascular invasion, lymph metastasis, and lymphatic invasion, WHO grade, as well as the 5-year survival rate. MUC2 was significantly correlated with lymphatic invasion and WHO grade. MUC5AC was highly positive in gender, depth of tumor invasion, WHO grade, TNM, lymph metastasis, and lymphatic invasion. Moreover, cases with decreased MUC5AC expression were correlated with less 5-year survival. MUC6 was only related with lymphatic invasion.ConclusionOur meta-analysis showed that MUC1 and MUC5AC had prognostic value in GC detected by immunohistochemistry. MUC1 and MUC5AC were also associated with some other significant clinicopathological parameters. Moreover, MUC2 and MUC6 also exert their influence in lymphatic invasion. However, further enlarged study awaits to verify our conclusion to deeply explore the role of mucin family members in GC.